Prevalence and predictors of annual asthma reviews in Scottish primary care data: an observational study - Holly Tibble; Alexandria Ming Wai Chung (BJGP Open)
Background: People with asthma are recommended to have regular reviews in primary care, with assessment of symptoms, adjustment of treatment and self-management processes, and the delivery of a written action plan for emergencies. Aim: To investigate the incidence and factors associated with attendance of annual asthma reviews. Design & setting: This observational study used electronic health records for 49 307 patients in Scotland with asthma between 1 January 2000 and 31 March 2017. The analysis population of 13 726 patients had at least five asthma-related encounters between 2008 and 2016. Method: Multivariable logistic regression was employed, using linked primary care prescription data and primary care registration demographic data. Results: There was a median of 381 days between subsequent reviews. Reviews in the index year were strongly associated with reviews in the following year (odds ratio [OR] 1.76, 95% confidence interval [CI] 1.68 to 1.84). In contrast, asthma consultations (excluding reviews) in the index year were associated with lower odds of having a review in the following year (OR 0.48, 95% CI = 0.46 to 0.51). Those aged 18–35 years in the index year or those with missing addresses in the practice registration data were the least likely groups to have an asthma review in the following year. Conclusion: Reviewing the delivery of asthma care identifies patients who may be slipping through the gaps by receiving only reactive asthma care rather than the structured, preventive care that can be delivered through annual reviews. Understanding the risk factors for not receiving an annual review can be leveraged to create more effective review invitations, such as explaining the specific content of reviews, introducing new contact methods to improve health equity, and reviewing the algorithm used to determine who is invited.